Rebuilding the past: East German preservationists as 'time activists'. Issue 4 (4th July 2021) - Colla, Marcus
ABSTRACT: This article examines how political time in the German Democratic Republic (GDR) was shaped and contested by architectural preservation during that state's formative years. In particular, it investigates the role of historic preservationists in the GDR as 'time activists' who both contributed to and challenged the construction of an ideologically informed 'order of time'. It argues that preservationists in the GDR helped mould, solidify and reinforce ideas of history and time in the physical environments of East German cities, sometimes to the great frustration of the ruling Socialist Unity Party, but at other times in accordance with the party's general objectives.